Princípios didáticos para o ensino de evolução biológica na perspectiva da pedagogia histórico-crítica - Pereira, Lucas Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the centrality and the importance of the Biological Evolution (EB) theme for the Biology teaching and the detachment of this practice with critical perspectives of education, this work aims to analyze the possibilities of the joint of EB teaching with the theoretical-methodological principles stated by Historical-Critical Pedagogy. It is characterized as a theoretical study, grounded on historical and dialectical materialism. It was appointed, as synthesis, three general didactic principles for the EB teaching on this pedagogical theory's perspective: dialectic conception of transmission-appropriation of the evolutionary theories knowledge; plain commitment with student's worldview formation; and the articulation of didactic components with the specificity of school education. We conclude that these principles may substantiate in different ways on teacher's labor and that other efforts shall sum to this in order to intervene, by the classical knowledge teaching, on the transformation of capitalist social relations

Considerando a centralidade e a importância dos conteúdos de Evolução Biológica (EB) para o ensino de Biologia e o distanciamento desta prática com as perspectivas críticas de educação, este trabalho possui o objetivo de analisar possibilidades de articulação do ensino de EB com princípios teórico-metodológicos propostos pela Pedagogia Histórico-Crítica. Caracteriza-se como um estudo teórico, fundamentado no materialismo histórico-dialético. Apontamos, como síntese, três princípios didáticos gerais para o ensino de EB na perspectiva desta teoria pedagógica: concepção dialética de transmissão-apropriação do conhecimento das teorias evolutivas; compromisso claro na formação da concepção de mundo de alunos e alunas; e articulação dos constituintes didáticos com a especificidade da educação escolar. Concluímos que estes princípios podem se constituir de diferentes maneiras no trabalho do/a professor/a e que outros esforços devem se somar a este para intervir, pelo ensino dos conhecimentos clássicos, na transformação das relações sociais capitalistas
Didactic principles for the Biological Evolution teaching on the perspective of Historical-Critical Pedagogy
Keywords: Biologia - Estudo e ensino; Evolução (Biologia); Pedagogia critica; Evolution (Biology)